2005
DOI: 10.1152/ajpcell.00343.2004
|View full text |Cite
|
Sign up to set email alerts
|

Insulin-induced phosphorylation of ENaC correlates with increased sodium channel function in A6 cells

Abstract: The purpose of this study was to determine whether there is a correlation between phosphorylation and activity of the epithelial sodium channel (ENaC). The three subunits that form the channel were immunoprecipitated from A6 cells by using specific polyclonal antibodies after labeling cells with 35 S or 32 P. When immune complexes were resolved on SDS-PAGE, the ␣-subunit migrated at 85 and 65 kDa, the ␤-subunit at 115 and 100 kDa, and the ␥-subunit at 90 kDa. In the resting state all three subunits were phosph… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

5
33
0

Year Published

2005
2005
2014
2014

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 43 publications
(38 citation statements)
references
References 16 publications
5
33
0
Order By: Relevance
“…It is conceivable that inhibition of outer renal medullary CYP4A isoforms is a mechanism by which insulin increases sodium reabsorption at the thick ascending limb, because insulin also exerts this action at the proximal tubule by translational and posttranslational activation of the NHE3 isoform of the Na ϩ /H ϩ exchanger 30 ; at the thiazide-sensitive Na ϩ Cl Ϫ transporter via diminished expression of WNK4 kinase 31 ; and at the epithelial sodium channel, via phosphorylation and translocation of the 3 channel subunits to the membrane. 32 This publication extends our previous observations in 2 regards. First, whereas Dahl-S rats are an inbred strain in which salt sensitivity of blood pressure coexists with insulin resistance, 18 salt-sensitive hypertensive subjects are not always insulin resistant.…”
Section: Discussionsupporting
confidence: 88%
“…It is conceivable that inhibition of outer renal medullary CYP4A isoforms is a mechanism by which insulin increases sodium reabsorption at the thick ascending limb, because insulin also exerts this action at the proximal tubule by translational and posttranslational activation of the NHE3 isoform of the Na ϩ /H ϩ exchanger 30 ; at the thiazide-sensitive Na ϩ Cl Ϫ transporter via diminished expression of WNK4 kinase 31 ; and at the epithelial sodium channel, via phosphorylation and translocation of the 3 channel subunits to the membrane. 32 This publication extends our previous observations in 2 regards. First, whereas Dahl-S rats are an inbred strain in which salt sensitivity of blood pressure coexists with insulin resistance, 18 salt-sensitive hypertensive subjects are not always insulin resistant.…”
Section: Discussionsupporting
confidence: 88%
“…Furthermore, insulin may acutely alter ENaC activity by mechanisms in addition to trafficking, perhaps by changing open probability or activity of existing channels. For example, Canessa and associates (136,169) have demonstrated that insulin phosphorylates ENaC subunits in both transfected Madin-Darby canine kidney cells and endogenously ENaC-expressing A6 cells. In A6 cells, this phosphorylation occurred on all three subunits and was associated with increased activity (169).…”
Section: Regulation Of Sodium Transport Proteins Along the Renal Tubumentioning
confidence: 99%
“…For example, Canessa and associates (136,169) have demonstrated that insulin phosphorylates ENaC subunits in both transfected Madin-Darby canine kidney cells and endogenously ENaC-expressing A6 cells. In A6 cells, this phosphorylation occurred on all three subunits and was associated with increased activity (169). Figure 2 illustrates how insulin might increase sodium reabsorption in the CD principal cell by activating both ENaC and Na-K-ATPase.…”
Section: Regulation Of Sodium Transport Proteins Along the Renal Tubumentioning
confidence: 99%
“…Thus, Liddle syndrome, a form of severe salt-sensitive hypertension, is caused by gain of function mutations/truncations in the channel ␤ or ␥ subunits (3,10,11), whereas loss of function mutations are associated with the hypotensive phenotype of pseudohypoaldosteronism type 1 (3,10,12). ENaC gating is regulated by hormones such as aldosterone, insulin, and EGF (13)(14)(15)(16). EGF inhibits ENaC (15,16) by mechanisms that involve an ERK1/2-catalyzed threonine phosphorylation of ENaC␤ and ENaC␥ (17,18).…”
mentioning
confidence: 99%